1999
DOI: 10.1007/bf01279262
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal changes in xylem pressure and mesophyll cell turgor pressure of the lianaTetrastigma voinierianum: The role of cell turgor in long-distance water transport

Abstract: Summary. Long-term xylem pressure measurements were performed on the liana Tetrastigma voinierianum (grown in a tropical greenhouse) between heights of 1 m and 9.5 m during the summer and autumn seasons with the xylem pressure probe. Simultaneously, the light intensity, the temperature, and the relative humidity were recorded at the measuring points. Parallel to the xylem pressure measurements, the diurnal changes in the cell turgor and the osmotic pressure of leaf cells at heights of 1 m and 5 m (partly also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
41
2

Year Published

1999
1999
2002
2002

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 45 publications
7
41
2
Order By: Relevance
“…In both cell types, the change is largely attributable to an increase in the osmotic pressure of the protoplast. This increase in PBS turgor pressure is very different from the observation of Thurmer et al (1999) who demonstrated that an increase in transpiration led to a decrease in the mesophyll cell turgor as well as xylem pressure. Considering the pathway of water flow from rhizosphere to the point of evaporation in terms of an electrical circuit model as described by Molz and Ferrier (1982), this indicates that, relative to the hydraulic resistance of the leaf (from PBS or mesophyll to the evaporation point), the hydraulic resistance to water flow from rhizosphere to leaf was considerably greater over the 9.5 m of the liana compared with the 0.2-0.3 m of barley.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…In both cell types, the change is largely attributable to an increase in the osmotic pressure of the protoplast. This increase in PBS turgor pressure is very different from the observation of Thurmer et al (1999) who demonstrated that an increase in transpiration led to a decrease in the mesophyll cell turgor as well as xylem pressure. Considering the pathway of water flow from rhizosphere to the point of evaporation in terms of an electrical circuit model as described by Molz and Ferrier (1982), this indicates that, relative to the hydraulic resistance of the leaf (from PBS or mesophyll to the evaporation point), the hydraulic resistance to water flow from rhizosphere to leaf was considerably greater over the 9.5 m of the liana compared with the 0.2-0.3 m of barley.…”
Section: Discussioncontrasting
confidence: 73%
“…In sugar beet plants, an inverse relationship between stomatal conductance and turgor pressure was demonstrated by Palta et al (1987). Thurmer et al (1999) found a similar diurnal change in turgor pressure in mesophyll cells of Tetrastigma, with the amplitude dependent on irradiance. However, there was a non-linear relation between transpiration and turgor pressure in mesophyll and epidermal cells of Tradescantia (Nonami and Schulze 1989).…”
Section: Discussionmentioning
confidence: 87%
“…in the liana T. voinierianum, Benkert et al, 1995 ;Zimmermann et al, 1995a,b ;Thu$ rmer et al, 1999 ;and in sugarcane and crop plants, F. Thu$ rmer et al, unpublished data ;Schneider et al, 1997a,b ;Wegner & Zimmermann, 1998).…”
Section: mentioning
confidence: 99%
“…Because of the quite tight hydraulic link water equilibrium should exist between the vessels and the tissue cells at any time (Balling & Zimmermann, 1990 ;Zimmermann et al, 1995a,b ;Thu$ rmer et al, 1999) :…”
Section: mentioning
confidence: 99%
“…Since, in the preceding paragraph, we have refuted the doubts concerning the validity of the xylem pressure recordings, we see no reason to question the osmotic values calculated by means of eq. 3 (Thtirmer et al 1999). We are aware, of course, that osmometry of reliably taken xylem sap samples is needed.…”
mentioning
confidence: 96%